Regional Human Rights Protection Systems Outside Europe - Dóra Szikszai, Laura Kovács-Berényi; Zombory, Katarzyna (2026)
The “Regional Human Rights Protection Systems Outside Europe” book provides foundational knowledge and a deeper understanding of the principal regional human rights mechanisms beyond the European framework: the Inter-American, African, Islamic and Asian systems. Bringing together leading experts in the field, the volume explores the foundations of these regional human rights systems within their historical, cultural and political contexts. Although regional human rights frameworks play an increasingly important role in the global human rights architecture, they remain comparatively understudied by European readers in relation to the universal and European human rights systems.The book is divided into four parts. The first examines the Inter-American system, while the second focuses on the African regional framework. The third broadens the discussion to Islamic and Asian perspectives, including an analysis of the approach adopted within the Commonwealth of Independent States (CIS). The fourth offers a comparative analysis of the mutual influence between the Inter-American and European human rights systems, highlighting the importance of understanding the diversity of regional approaches to human rights protection.The contributors are scholars from Central and Eastern Europe with specialised expertise in international human rights law. Their research on regional human rights systems beyond Europe was supported through valuable collaboration with peer reviewers whose deep understanding of these regions is based on professional experience and close academic ties to respective human rights systems.This volume is intended as a valuable resource for scholars, practitioners and public officials seeking a comprehensive introduction to the world's regional human rights systems, their achievements and challenges, and the role of regional and cultural factors in the development of international human rights protection.